Improving Stress Management of a Nursing Staff in a Post-Anesthesia Care Unit - Selvaggio, Jessica (My University, 2019)
Healthcare workers, especially nurses, experience high levels of stress every day due to the high demands of their jobs. Persistently high levels of stress can negatively impact an individual’s physical, mental, and psychological well-being while also effecting their job satisfaction and work performance. These conditions can eventually lead to high employee turnover and poor patient outcomes. Educating nurses about the importance of developing healthy stress management skills can help to prevent the development of negative coping habits, improve overall well-being, and improve patient care. Stress management interventions were implemented in the high stress environment of a post-anesthesia care unit. The nursing staff was familiarized with mindfulness-based practices. A stress management education session was presented at their staff meeting. The staff received weekly emails containing stress reduction strategies and they were encouraged to practice these strategies daily. Nurses were also challenged to perform a 1-minute daily meditation prior to beginning each shift. The interventions were evaluated using a pre and post-implementation survey containing items from the Perceived Stress Scale and the Mindful Attention Awareness Scale. Demonstrated by data comparison, the perceived level of stress within the unit was reduced after the implementation period and the states of mindfulness, attention, and awareness were increased among the nurses. The effectiveness, feasibility, and low budget of this project made it easily replicable throughout other departments and institutions.
Keywords: Stress; Stress Management; Inpatient Nursing; Stress Reduction; Burnout; Mindfulness-based Cognitive Therapy